Individualized breast cancer therapy using Mcl-1 inhibition based combination - Bashari, Muhammad Hasan; Malvestiti, Stefano; Fan, Fengjuan; Vallet, Sonia; Jäger, Dirk; Podar, Klaus (Annals of oncology, 2016)
© European Society for Medical Oncology 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Breast cancer (BC) is leading cause of cancer-related mortality in women. Anti-apoptotic Bcl-2 family members including Bcl-2, Bcl-xL and myeloid cell leukemia-1 (Mcl-1) control the intrinsic pathway of apoptosis. Elevated Mcl-1 levels have been correlated with poor prognosis. The aim of this study is to evaluate a rationally-derived combination of Mcl-1-inhibitor with Bcl-2 or Bcl-xL inhibitors as well as with conventional BC treatment and to provide the derived rationale to therapeutically target Mcl-1.Methods: The anti-BC cell-activity of the novel small molecule Mcl-1 inhibitor EU5346 was evaluated alone or in combination with other antiapoptotic agents, hormone therapy, targeted therapy, or chemotherapy using proliferation and spheroid forming assays as well as immunoblotting in different BC cell lines. Synergistic activity of combination...
Gesehen am 11.09.2017